Wnt/β-Catenin-Responsive Cells in Prostatic Development and Regeneration. (29th July 2015) - Lee, Suk Hyung; Johnson, Daniel T.; Luong, Richard; Yu, Eun Jeong; Cunha, Gerald R.; Nusse, Roel; Sun, Zijie
Abstract : The precise role of Wnt/β-catenin signaling during prostatic development and tumorigenesis is unclear. Axin2 is a direct transcriptional target of β-catenin. Recent studies have shown that Axin2 -expressing cells have stem/progenitor cell properties in a variety of mouse tissues. Here, we genetically labeled Axin2 -expressing cells at various time points and tracked their cellular behavior at different developmental and mature stages. We found that prostatic Axin2 -expressing cells mainly express luminal epithelial cell markers and are able to expand luminal cell lineages during prostatic development and maturation. They can also survive androgen withdrawal and regenerate prostatic luminal epithelial cells following androgen replacement. Deletion of β-catenin or expression of stabilized β-catenin in these Axin2 -expressing cells results in abnormal development or oncogenic transformation, respectively. Our study uncovers a critical role of Wnt/β-catenin-responsive cells in prostatic development and regeneration, and that dysregulation of Wnt/β-catenin signaling in these cells contributes to prostatic developmental defects and tumorigenesis. Stem Cells   2015;33:3356–3367